Theoretical insights into the superior activity of gold catalysts and reactions of organogold intermediates with electrophiles - Hashmi, A. Stephen K.; Pernpointner, Markus; Hansmann, Max M. (Gold, 2011)
Three fundamental steps of homogeneous gold catalysis, the activiation of substrates by coordination to gold, the protodeauration after the nucleophilic addition and the transmetalation to palladium in palladium-catalysed C-C bond forming reactions using organogold intermediates have been studied and discussed in detail.
Gesehen am 07.09.2022